Guidelines for the management of vitiligo: the European Dermatology Forum consensus. (2nd November 2012) - Taieb, A.; Alomar, A.; Böhm, M.; Dell'Anna, M.L.; De Pase, A.; Eleftheriadou, V.; Ezzedine, K.; Gauthier, Y.; Gawkrodger, D.J.; Jouary, T.; Leone, G.; Moretti, S.; et al.
Summary The aetiopathogenic mechanisms of vitiligo are still poorly understood, and this has held back progress in diagnosis and treatment. Up until now, treatment guidelines have existed at national levels, but no common European viewpoint has emerged. This guideline for the treatment of segmental and nonsegmental vitiligo has been developed by the members of the Vitiligo European Task Force and other colleagues. It summarizes evidence‐based and expert‐based recommendations (S1 level).